Energy storage device positive electrode material, preparation method and modified energy storage device
The lithium ion channel is formed by using the first composite material layer of porous mesh aluminum sulfate and phenolic resin glue in the positive electrode material of the lithium-ion battery to form a lithium-ion channel, and the positive electrode material is solved by using the first composite material layer of porous hollow spherical zirconium oxide particles. The side reaction problems caused by direct contact with the electrolyte significantly extend the service life of the battery.
Patent Information
- Application Number
- CN202010931179.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-09-07
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2040-09-07
AI Technical Summary
In existing lithium-ion batteries, the positive electrode material is in direct contact with the electrolyte, resulting in an increase in side reactions and reducing the battery life.
A structural design is adopted including a positive electrode active material layer, a first composite material layer and a second composite material layer. The first composite material layer is a porous mesh-shaped mixture of aluminum sulfate and phenolic resin glue, and the second composite material layer is porous hollow spherical zirconia particles, forming a channel through which lithium ions pass, preventing direct contact between the positive electrode material and the electrolyte.
The side reaction between the electrolyte and the positive electrode active material layer is significantly reduced, the service life of the battery is extended, and the stability of the positive electrode material is enhanced by the coating of zirconium oxide.
Smart Images

Figure CN111969213B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage devices, and more specifically, to a positive electrode material for an energy storage device, a preparation method, and a modified energy storage device. Background Art
[0002] Lithium batteries include lithium-ion batteries and lithium batteries. Lithium batteries mainly use pure lithium metal as electrodes. Since lithium metal is relatively active, lithium batteries are more dangerous. Based on this situation, we generally use lithium-ion batteries in our daily lives, such as in computers and other electronic devices.
[0003] Lithium-ion battery is a secondary battery that mainly relies on the movement of lithium ions between the positive electrode and the negative electrode to work. During the charge and discharge process, Li+ is intercalated and deintercalated between the two electrodes: when charging, Li+ is deintercalated from the positive electrode and intercalated into the negative electrode through the electrolyte, and the negative electrode is in a lithium-rich state; the opposite is true during discharge.
[0004] The embedding or de-embedding process of lithium ions in the process of going back and forth between the two electrodes is realized in the positive or negative electrode material. Since the mass ratio of positive and negative electrode materials is 3: 1-4: 1, the performance of the positive electrode material directly affects the performance of the lithium-ion battery, and its cost also directly determines the cost of the battery. In the prior art, active materials such as lithium cobalt oxide, lithium manganese oxide or lithium iron phosphate are generally directly mixed with adhesives and conductive agents and coated on the current collector, and then placed in the battery to directly contact the electrolyte. This will cause the positive electrode material to be in direct contact with the electrolyte. After multiple charge and discharge cycles, the positive electrode material will react with the electrolyte, reducing the service life of the battery. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the present invention provides a positive electrode material for an energy storage device, a preparation method and a modified energy storage device, specifically a positive electrode material for an energy storage device, a preparation method and a modified lithium-ion battery, which can greatly reduce the side reactions of the electrolyte and the lithium-ion positive electrode active material layer, thereby improving the battery life.
[0006] The technical solution adopted by the present invention to solve its technical problem is: a positive electrode material for an energy storage device, the improvement of which is that it includes a positive electrode active material layer, a first composite material layer and a second composite material layer;
[0007] The first composite material layer is coated on the outer surface of the positive electrode active material layer, and the first composite material layer is in a porous mesh shape; the second composite material is coated on the first composite material layer, and the second composite material layer is zirconium oxide particles, and the zirconium oxide particles are in a porous hollow spherical shape;
[0008] After the holes on the first composite material layer are connected with the holes on the second composite material layer, channels for lithium ions to pass through are formed.
[0009] In the above structure, the positive electrode active material is one of lithium cobalt oxide, lithium manganese oxide, ternary material and lithium iron phosphate.
[0010] In the above structure, the first composite material layer is a mixture of aluminum sulfate and phenolic resin glue.
[0011] In the above structure, the weight ratio of aluminum sulfate to phenolic resin glue is 1:3.
[0012] In the above structure, the diameter of the holes on the first composite material layer is 10-15 nm.
[0013] In the above structure, the diameter of the pores on the zirconium oxide particles is 15-20 nm.
[0014] On the other hand, the present invention also provides a method for preparing a positive electrode material for an energy storage device, wherein the improvement is that the preparation method comprises the following steps:
[0015] S1, preparation of coating liquid, adding phenolic resin glue, sodium salt and aluminum salt in a mass ratio of 3:1:1 into a first solvent, the weight ratio of phenolic resin glue to the first solvent being 2:1, and stirring and mixing to obtain a coating liquid;
[0016] S2, preparing a solid-liquid mixture, mixing the positive electrode active material and the coating liquid in a mass ratio of 1:1 to obtain a solid-liquid mixture;
[0017] S3, first drying and sintering, drying the solid-liquid mixture under the protection of inert gas, the drying temperature is 60-90°C, the time is 2-3h, and then sintering, the sintering temperature is 500-800°C, the time is 1-2h, and the first composite material layer is formed on the outer surface of the positive electrode active material;
[0018] S4, adding zirconium oxide particles, dispersing the sintered material in step S3 in the second solvent, and then adding porous hollow spherical zirconium oxide particles to the second solvent, mixing evenly and filtering;
[0019] S5, second drying and sintering, drying the solid substance obtained by filtration in step S4 under the protection of inert gas, the drying temperature is 70-80°C, the time is 2-3h, and then sintering is performed, the sintering temperature is 700-900°C, and the sintering time is 3-5h, to obtain the positive electrode material of the energy storage device.
[0020] Furthermore, in step S1, the aluminum salt is aluminum phosphate or aluminum sulfate.
[0021] Furthermore, in step S1, the first solvent is ethanol or methanol.
[0022] Furthermore, in step S4, the second solvent is water.
[0023] Furthermore, in the step S4, the mass ratio of the sintered material in step S3, the second solvent and the zirconium oxide particles is 1:2:1.
[0024] Furthermore, in step S4, the steps of making zirconium oxide particles are as follows:
[0025] S41, mixing zirconium oxide powder and sodium salt in a mass ratio of 1:2 to form a mixture;
[0026] S42, using a mixing granulator to granulate the mixture in step S41 into spherical particles, then adding the spherical particles into excess water, filtering and drying in sequence to obtain solid particles, thereby obtaining porous hollow spherical zirconium oxide particles.
[0027] Furthermore, in step S1 and step S41, the sodium salt is one or more of sodium chloride, sodium sulfate and sodium nitrate.
[0028] Furthermore, the diameter of the sodium salt is 10-15 nm.
[0029] On the other hand, the present invention also provides a modified energy storage device, including a positive electrode plate, a negative electrode plate and an electrolyte, wherein the improvement is that the positive electrode plate includes an energy storage device positive electrode material prepared by the preparation method of the energy storage device positive electrode material as described above.
[0030] The beneficial effects of the present invention are: a porous mesh structure is formed in the first composite material layer, and the second composite material adopts porous hollow spherical zirconium oxide particles. When the second composite material layer is coated on the surface of the first composite material layer, a channel for only lithium ions to pass through is formed, avoiding direct contact between the positive electrode material and the electrolyte, greatly reducing the side reaction between the electrolyte and the lithium ion positive electrode active material layer, thereby improving the battery life. At the same time, since the second composite material layer is zirconium oxide particles, zirconium oxide itself has the advantages of stable high-temperature chemical properties, corrosion resistance, and oxidation resistance, and is coated on the outermost layer of the positive electrode active material, which can greatly increase the service life of the entire positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic structural diagram of a positive electrode material for an energy storage device of the present invention.
[0032] Figure 2 The present invention is a schematic flow chart of a method for preparing a positive electrode material for an energy storage device. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0034] The following will clearly and completely describe the concept, specific structure and technical effects of the present invention in combination with the embodiments and drawings, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. In addition, all the connection / connection relationships involved in the patent do not refer to the direct connection of components, but refer to the formation of a better connection structure by adding or reducing connection accessories according to the specific implementation situation. The various technical features in the invention can be combined interchangeably without conflicting with each other.
[0035] Reference Figure 1 As shown, the present invention discloses a positive electrode material for an energy storage device, specifically a positive electrode material for a lithium-ion battery, wherein the positive electrode material for the lithium-ion battery comprises a positive electrode active material layer 10, a first composite material layer 20 and a second composite material layer 30; wherein the positive electrode active material layer 10 adopts a material commonly used in the prior art, for example, it can be one of lithium cobalt oxide, lithium manganese oxide, a ternary material and lithium iron phosphate. In the present embodiment, the positive electrode active material layer 10 is lithium cobalt oxide, which is a conventional selection method in the prior art, and therefore will not be described in detail in the present embodiment.
[0036] Further, such as Figure 1 As shown, the first composite material layer 20 is coated on the outer surface of the positive electrode active material layer 10, and the first composite material layer 20 is in a porous mesh shape, so there are several holes on the first composite material layer 20, and the diameter of the holes is in the range of 10-15nm. The first composite material layer 20 wraps the positive electrode active material layer 10. In this embodiment, the first composite material layer 20 is a mixture of aluminum sulfate and phenolic resin glue, and the weight ratio of aluminum sulfate to phenolic resin glue is 1:3, so that the phenolic resin glue can coat aluminum sulfate to form a porous mesh structure; the second composite material is coated on the first composite material layer 20, and the second composite material layer 30 is zirconium oxide particles, and the zirconium oxide particles are in a porous hollow spherical shape, and the diameter of the holes on the zirconium oxide particles is 15-20nm. In this embodiment, after the zirconium oxide particles are combined with the first material composite layer, the holes on the first composite material layer 20 are connected with the holes on the zirconium oxide, forming a channel for lithium ions to pass through.
[0037] The lithium-ion battery positive electrode material of the present invention forms a porous mesh structure in the first composite material layer 20, and the second composite material adopts porous hollow spherical zirconium oxide particles. When the second composite material layer 30 is coated on the surface of the first composite material layer 20, a channel for only lithium ions to pass through will be formed, avoiding direct contact between the positive electrode material and the electrolyte, greatly reducing the side reaction between the electrolyte and the lithium ion positive electrode active material layer 10, thereby improving the battery life. At the same time, since the second composite material layer 30 is zirconium oxide particles, zirconium oxide itself has the advantages of stable high-temperature chemical properties, corrosion resistance, and oxidation resistance. Coating it on the outermost layer of the positive electrode active material can greatly increase the service life of the entire positive electrode material. In addition, the first composite material layer 20 adopts a mixture of aluminum sulfate and phenolic resin glue, and aluminum sulfate is conducive to forming a solid solution state of the active material, thereby stabilizing the lattice and improving the cycle performance.
[0038] Example 1
[0039] Combination Figure 2 As shown, for the positive electrode material of the energy storage device, that is, the positive electrode material of the lithium ion battery, the present invention also provides a preparation method suitable for the positive electrode material of the lithium ion battery. In this embodiment, the preparation method includes the following steps:
[0040] S1, preparation of coating liquid, adding phenolic resin glue, sodium salt and aluminum salt in a mass ratio of 3:1:1 into a first solvent, stirring and mixing to obtain a coating liquid; wherein the phenolic resin glue is a type of glue made of phenolic resin, and has a viscosity range of 4000-5000cps / 25° and a solid content of 20-25%; the weight ratio of the phenolic resin glue to the first solvent is 2:1;
[0041] S2, preparing a solid-liquid mixture, mixing the positive electrode active material and the coating liquid in a mass ratio of 1:1 to obtain a solid-liquid mixture;
[0042] S3, first drying and sintering, drying the solid-liquid mixture under the protection of inert gas at a temperature of 60° C. for 3 hours, and then sintering at a temperature of 500° C. for 2 hours to form a first composite material layer 20 on the outer surface of the positive electrode active material;
[0043] S4, adding zirconium oxide particles, dispersing the sintered material in step S3 in the second solvent, and then adding porous hollow spherical zirconium oxide particles to the second solvent, mixing evenly and filtering, wherein the mass ratio of the sintered material in step S3, the second solvent and the zirconium oxide particles is 1:2:1;
[0044] In this embodiment, the second solvent is water, which is used to contain the sodium salt and form holes on the first composite material layer 20;
[0045] S5, second drying and sintering, drying the solid substance obtained by filtration in step S4 under the protection of inert gas, the drying temperature is 70° C., the time is 3 hours, and then sintering is performed, the sintering temperature is 700° C., and the sintering time is 5 hours, to obtain a positive electrode material for a lithium ion battery.
[0046] In the above embodiment, the first solvent is ethanol, which dissolves the sodium salt and forms holes on the first composite material layer 20. The porous hollow spherical zirconium oxide particles can be coated on the surface of the holes to form a channel through which lithium ions can pass freely, while reducing the contact between the electrolyte and the positive electrode material and reducing the occurrence of side reactions.
[0047] In addition, in step S4, the steps for preparing zirconium oxide particles are as follows:
[0048] S41, mixing zirconium oxide powder and sodium salt in a mass ratio of 1:2 to form a mixture;
[0049] S42, using a mixing granulator to granulate the mixture in step S41 into spherical particles with a diameter of 15-20 nm, then adding the spherical particles into excess water, filtering and drying in sequence to obtain solid particles, thereby obtaining porous hollow spherical zirconium oxide particles.
[0050] It should be noted that in the above-mentioned step S1 and step S41, the sodium salt is one or more of sodium chloride, sodium sulfate and sodium nitrate. In this embodiment, the sodium salt is sodium chloride. And the diameter of the sodium salt is 10-15nm. In the above-mentioned step S1, the aluminum salt used is aluminum phosphate or aluminum sulfate. In this embodiment, the aluminum salt used is aluminum phosphate, which is insoluble in methanol or ethanol.
[0051] Based on this, the preparation method of the positive electrode material of the lithium ion battery of the present invention, the first layer of composite material contains aluminum elements, stabilizes the lattice of the positive electrode active material, improves the cycle performance of the battery, and coats a layer of spherical porous hollow spherical zirconium oxide outside the first composite material. The holes on the first layer of composite material will not only connect with the holes on the hollow porous spherical zirconium oxide particles to form a channel for lithium ions to pass through, but also reduce the contact reaction between the electrolyte and the positive electrode material, and improve the service life of the battery. In addition, zirconium oxide itself has the advantages of stable high-temperature chemical properties, corrosion resistance, and oxidation resistance. Coating it on the outermost layer of the positive electrode active material can also greatly increase the service life of the entire positive electrode material.
[0052] Example 2
[0053] Combination Figure 2As shown, for the positive electrode material of the energy storage device, that is, the positive electrode material of the lithium ion battery, the present invention also provides a preparation method suitable for the positive electrode material of the lithium ion battery. In this embodiment, the preparation method includes the following steps:
[0054] S1, preparation of coating liquid, adding phenolic resin glue, sodium salt and aluminum salt in a mass ratio of 3:1:1 into a first solvent, the weight ratio of phenolic resin glue to the first solvent being 2:1, and stirring and mixing to obtain a coating liquid;
[0055] S2, preparing a solid-liquid mixture, mixing the positive electrode active material and the coating liquid in a mass ratio of 1:1 to obtain a solid-liquid mixture;
[0056] S3, first drying and sintering, drying the solid-liquid mixture under the protection of inert gas at a temperature of 90° C. for 2 h, and then sintering at a temperature of 800° C. for 1 h, to form a first composite material layer 20 on the outer surface of the positive electrode active material;
[0057] S4, adding zirconium oxide particles, dispersing the sintered material in step S3 in the second solvent, and then adding porous hollow spherical zirconium oxide particles to the second solvent, mixing evenly and filtering, wherein the mass ratio of the sintered material in step S3, the second solvent and the zirconium oxide particles is 1:2:1;
[0058] In this embodiment, the second solvent is water, which is used to contain the sodium salt and form holes on the first composite material layer 20;
[0059] S5, second drying and sintering, drying the solid substance obtained by filtration in step S4 under the protection of inert gas, the drying temperature is 80° C., the time is 2 h, and then sintering is performed, the sintering temperature is 900° C., and the sintering time is 3 h, to obtain a positive electrode material for a lithium ion battery.
[0060] In the above embodiment, the first solvent is ethanol, which dissolves the sodium salt and forms holes on the first composite material layer 20. The porous hollow spherical zirconium oxide particles can be coated on the surface of the holes to form a channel through which lithium ions can pass freely, while reducing the contact between the electrolyte and the positive electrode material and reducing the occurrence of side reactions.
[0061] In addition, in step S4, the steps for preparing zirconium oxide particles are as follows:
[0062] S41, mixing zirconium oxide powder and sodium salt in a mass ratio of 1:2 to form a mixture;
[0063] S42, using a mixing granulator to granulate the mixture in step S41 into spherical particles with a diameter of 15-20 nm, then adding the spherical particles into excess water, filtering and drying in sequence to obtain solid particles, thereby obtaining porous hollow spherical zirconium oxide particles.
[0064] It should be noted that in the above-mentioned step S1 and step S41, the sodium salt is one or more of sodium chloride, sodium sulfate and sodium nitrate. In this embodiment, the sodium salt is sodium chloride. And the diameter of the sodium salt is 10-15nm. In the above-mentioned step S1, the aluminum salt used is aluminum phosphate or aluminum sulfate. In this embodiment, the aluminum salt used is aluminum phosphate, which is insoluble in methanol or ethanol.
[0065] Based on this, the preparation method of the positive electrode material of the lithium ion battery of the present invention, the first layer of composite material contains aluminum elements, stabilizes the lattice of the positive electrode active material, improves the cycle performance of the battery, and coats a layer of spherical porous hollow spherical zirconium oxide outside the first composite material. The holes on the first layer of composite material will not only connect with the holes on the hollow porous spherical zirconium oxide particles to form a channel for lithium ions to pass through, but also reduce the contact reaction between the electrolyte and the positive electrode material, and improve the service life of the battery. In addition, zirconium oxide itself has the advantages of stable high-temperature chemical properties, corrosion resistance, and oxidation resistance. Coating it on the outermost layer of the positive electrode active material can also greatly increase the service life of the entire positive electrode material.
[0066] Example 3
[0067] Combination Figure 2 As shown, for the positive electrode material of the energy storage device, that is, the positive electrode material of the lithium ion battery, the present invention also provides a preparation method suitable for the positive electrode material of the lithium ion battery. In this embodiment, the preparation method includes the following steps:
[0068] S1, preparation of coating liquid, adding phenolic resin glue, sodium salt and aluminum salt in a mass ratio of 3:1:1 into a first solvent, the weight ratio of phenolic resin glue to the first solvent being 2:1, and stirring and mixing to obtain a coating liquid;
[0069] S2, preparing a solid-liquid mixture, mixing the positive electrode active material and the coating liquid in a mass ratio of 1:1 to obtain a solid-liquid mixture;
[0070] S3, first drying and sintering, drying the solid-liquid mixture under the protection of inert gas at a temperature of 75° C. for 2.5 h, and then sintering at a temperature of 650° C. for 1.5 h to form a first composite material layer 20 on the outer surface of the positive electrode active material;
[0071] S4, adding zirconium oxide particles, dispersing the sintered material in step S3 in the second solvent, and then adding porous hollow spherical zirconium oxide particles to the second solvent, mixing evenly and filtering; wherein the mass ratio of the sintered material, the second solvent and the zirconium oxide particles in step S3 is 1:2:1;
[0072] In this embodiment, the second solvent is water, which is used to dissolve the sodium salt and form holes on the first composite material layer 20;
[0073] S5, second drying and sintering, drying the solid substance obtained by filtration in step S4 under the protection of inert gas, the drying temperature is 75° C., the time is 2.5 hours, and then sintering, the sintering temperature is 800° C., and the sintering time is 4 hours, to obtain a positive electrode material for a lithium ion battery.
[0074] In the above embodiment, the first solvent is ethanol, which dissolves the sodium salt and forms holes on the first composite material layer 20. The porous hollow spherical zirconium oxide particles can be coated on the surface of the holes to form a channel through which lithium ions can pass freely, while reducing the contact between the electrolyte and the positive electrode material and reducing the occurrence of side reactions.
[0075] In addition, in step S4, the steps for preparing zirconium oxide particles are as follows:
[0076] S41, mixing zirconium oxide powder and sodium salt in a mass ratio of 1:2 to form a mixture;
[0077] S42, using a mixing granulator to granulate the mixture in step S41 into spherical particles with a diameter of 15-20 nm, then adding the spherical particles into excess water, filtering and drying in sequence to obtain solid particles, thereby obtaining porous hollow spherical zirconium oxide particles.
[0078] It should be noted that in the above-mentioned step S1 and step S41, the sodium salt is one or more of sodium chloride, sodium sulfate and sodium nitrate. In this embodiment, the sodium salt is sodium chloride. And the diameter of the sodium salt is 10-15nm. In the above-mentioned step S1, the aluminum salt used is aluminum phosphate or aluminum sulfate. In this embodiment, the aluminum salt used is aluminum sulfate, which is insoluble in methanol or ethanol.
[0079] Based on this, the preparation method of the positive electrode material of the lithium ion battery of the present invention, the first layer of composite material contains aluminum elements, stabilizes the lattice of the positive electrode active material, improves the cycle performance of the battery, and coats a layer of spherical porous hollow spherical zirconium oxide outside the first composite material. The holes on the first layer of composite material will not only connect with the holes on the hollow porous spherical zirconium oxide particles to form a channel for lithium ions to pass through, but also reduce the contact reaction between the electrolyte and the positive electrode material, and improve the service life of the battery. In addition, zirconium oxide itself has the advantages of stable high-temperature chemical properties, corrosion resistance, and oxidation resistance. Coating it on the outermost layer of the positive electrode active material can also greatly increase the service life of the entire positive electrode material.
[0080] Based on the above embodiments, the present invention also provides a modified energy storage device, namely a modified lithium-ion battery, comprising a positive electrode plate, a negative electrode plate and an electrolyte, wherein the positive electrode plate comprises the positive electrode material of the energy storage device prepared in any one of the embodiments.
[0081] In addition, in combination with the following table, the present invention also provides a test method for the service life of a battery, wherein the energy storage device in Example 1 and Example 2 in the following table, i.e., the preparation of a lithium-ion battery, is as follows: the positive electrode material adopts the above-mentioned positive electrode material of the present invention, and the positive electrode plate is composed of lithium iron phosphate, positive electrode conductive agent conductive graphite, binder polyvinylidene fluoride and positive electrode collector aluminum foil; the negative electrode plate is composed of negative electrode conductive agent conductive graphite, negative electrode binder styrene-butadiene rubber and negative electrode collector copper foil; the electrolyte is composed of lithium salt LiBF4, solvent dimethyl carbonate and additive fluoroethylene carbonate; thereafter, according to the normal lithium-ion battery production process, an energy storage device, i.e., a lithium-ion battery, is manufactured.
[0082] The lithium batteries used in Comparative Examples 1 and 2 in the following table are different from the lithium ion batteries in Examples 1 and 2 in that the outer surface of the positive electrode active material layer 10 is not coated with the first composite material layer 20 and the second composite material layer 30 .
[0083] The positive electrode sheet, the negative electrode sheet and the coated diaphragm are assembled into a button battery in a glove box filled with argon gas, and the battery capacity cycle test is carried out on a cycle charge and discharge tester. The specific data are as follows:
[0084]
[0085] Combined with the data in the above table, it can be seen that, whether it is the capacity before cycle charging or the capacity of cycle charging, the lithium ion battery prepared by the preparation method of the lithium ion battery positive electrode material of the present invention is larger than the lithium ion battery prepared by not adopting the preparation method of the present invention, and the capacity retention rate is relatively better.
[0086] The above is a specific description of the preferred implementation of the present invention, but the invention is not limited to the embodiments. Those skilled in the art can make various equivalent modifications or substitutions without violating the spirit of the present invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A positive electrode material for an energy storage device, characterized in that: comprising a positive electrode active material layer, a first composite material layer and a second composite material layer; The first composite material layer is coated on the outer surface of the positive electrode active material layer, and the first composite material layer is in a porous mesh shape; the second composite material layer is coated on the first composite material layer, and the second composite material layer is zirconium oxide particles, and the zirconium oxide particles are in a porous hollow spherical shape; After the holes on the first composite material layer are connected with the holes on the second composite material layer, a channel for lithium ions to pass through is formed; The first composite material layer is a mixture of aluminum sulfate and phenolic resin glue.
2. The positive electrode material for an energy storage device according to claim 1, characterized in that: The positive electrode active material is one of lithium cobalt oxide, lithium manganese oxide, ternary material and lithium iron phosphate.
3. The positive electrode material for an energy storage device according to claim 1, characterized in that: The weight ratio of the aluminum sulfate to the phenolic resin glue is 1:
3.
4. A positive electrode material for an energy storage device according to claim 1 or 3, characterized in that: The diameter of the holes on the first composite material layer is 10-15 nm.
5. The positive electrode material for an energy storage device according to claim 1, characterized in that: The diameter of the pores on the zirconium oxide particles is 15-20 nm.
6. A method for preparing a positive electrode material for an energy storage device, characterized in that: The preparation method comprises the following steps: S1, preparation of coating liquid, adding phenolic resin glue, sodium salt and aluminum salt in a mass ratio of 3:1:1 into a first solvent, the weight ratio of phenolic resin glue to the first solvent being 2:1, and stirring and mixing to obtain a coating liquid; S2, preparing a solid-liquid mixture, mixing the positive electrode active material and the coating liquid in a mass ratio of 1:1 to obtain a solid-liquid mixture; S3, first drying and sintering, drying the solid-liquid mixture under the protection of inert gas, the drying temperature is 60-90°C, the time is 2-3h, and then sintering, the sintering temperature is 500-800°C, the time is 1-2h, and the first composite material layer is formed on the outer surface of the positive electrode active material; S4, adding zirconium oxide particles, dispersing the sintered material in step S3 in the second solvent, and then adding porous hollow spherical zirconium oxide particles to the second solvent, mixing evenly and filtering; S5, second drying and sintering, drying the solid substance obtained by filtration in step S4 under the protection of inert gas, the drying temperature is 70-80°C, the time is 2-3h, and then sintering is performed, the sintering temperature is 700-900°C, and the sintering time is 3-5h, to obtain the positive electrode material of the energy storage device.
7. The method for preparing the positive electrode material of the energy storage device according to claim 6, characterized in that: In the step S1, the aluminum salt is aluminum phosphate or aluminum sulfate.
8. The method for preparing the positive electrode material of the energy storage device according to claim 6, characterized in that: In the step S1, the first solvent is ethanol or methanol.
9. The method for preparing the positive electrode material of the energy storage device according to claim 6, characterized in that: In the step S4, the second solvent is water.
10. The method for preparing the positive electrode material of the energy storage device according to claim 6, characterized in that: In the step S4, the mass ratio of the sintered material in step S3, the second solvent and the zirconium oxide particles is 1:2:
1.
11. The method for preparing the positive electrode material of the energy storage device according to claim 6, characterized in that: In step S4, the steps of preparing zirconium oxide particles are as follows: S41, mixing zirconium oxide powder and sodium salt in a mass ratio of 1:2 to form a mixture; S42, using a mixing granulator to granulate the mixture in step S41 into spherical particles, then adding the spherical particles into excess water, filtering and drying in sequence to obtain solid particles, thereby obtaining porous hollow spherical zirconium oxide particles.
12. The method for preparing the positive electrode material of the energy storage device according to claim 10, characterized in that: In step S1 and step S41, the sodium salt is one or more of sodium chloride, sodium sulfate and sodium nitrate.
13. The method for preparing the positive electrode material of the energy storage device according to claim 12, characterized in that: The diameter of the sodium salt is 10-15 nm.
14. A modified energy storage device, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The positive electrode plate comprises a positive electrode material prepared by the method for preparing a positive electrode material for an energy storage device as described in any one of claims 6-13.
Citation Information
Patent Citations
Energy storage device positive pole piece
CN212648280U